The diagnostic value of serum Neuroapoptosis-regulating invertase (NARC1), von Willebrand factor (vWF), and ‌Protein G3a levels in type 2 diabetes patients with macrovascular lesions: Serum NARC1, vWF, and G3a levels in T2DM with macrovascular lesions - Wang, Yangyang; Jia, Suilin; Cai, Haolin; Zhang, Yige; Lv, Shuangyan (Journal of Medical Biochemistry, 2026)
[Objective] To evaluate the diagnostic value of serum Neuroapoptosis-regulating invertase (NARC1), von Willebrand factor (vWF), and ‌Protein G3a levels in type 2 diabetes patients complicated with macrovascular lesions.[Methods] The type 2 diabetes group consisted of 420 patients with the disease who were admitted to the hospital between January 2021 and June 2024. 150 healthy people who visited this hospital for checkups within the same time frame were chosen to be part of the healthy control group. Based on the diagnostic criteria for macrovascular disease, individuals with type 2 diabetes were split into two groups: 236 patients with simple diabetes and 184 patients with macrovascular disease. The changes in the serum NARC1, vWF and ‌Protein G3a levels in each group were observed, serum NARC1, vWF, and ‌Protein G3a levels in individuals with type 2 diabetes were compared before and after treatment using univariate, and the diagnostic efficacy of the three indicators in macrovascular disease complicated with type 2 diabetes was analyzed.[Results] Serum NARC1 and vWF levels were significantly greater in the type 2 diabetes group, although serum ‌Protein G3a levels were significantly lower (P
Keywords: Type 2 diabetes; Macrovascular disease; Neuroapoptosis-regulating invertase; Von Willebrand factor; ‌Protein G3a